(3aUd aj Cf Gddg JYGdi Ndb GdbdH ddEfSGf jYde Hg GdCTjGAs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3bGd GdTjN Hf JjejI aUd Cf Gddg SHMGfg hJYGdi Ndb GdbdH ddEfSGf jYde Hg GdCTjGA ceG Ndb GdYjf jQi HgG GdCTjGA hGdCPf jSeY HgG GdCTjGA s
(3BNQgG (B:s
(3hdeG cGf jfUQa Yf GdHGWd agh Rci hSdje hGddg CYde HGdeQGO hGddg CYde hahb cd Pi Yde Ydje hGdMeO ddg GdYRjR GdhgGH GdcQje GdJhGH hMSHfG Gddg hfYe Gdhcjd JeJ hGdMeO ddg hMOg hUdi Gddg Ydi ef GdfHi HYOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG eWGdH ddcJGHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs